Characterization and phylogenetic analysis of the complete chloroplast genome of Carpesium lipskyi (Asteraceae, Inuleae) - Tingyu Li; Hui Chen; Xinyu Chen; Tianmeng Qu; Xinyi Zheng; Liang Pang; Xianhua Gu; Zhixi Fu (Mitochondrial DNA. Part B. Resources, 2024)
The species of Carpesium lipskyi C.Winkl. 1998 is an important traditional Chinese medicine in China. In this study, the complete chloroplast (cp) genome of C. lipskyi was determined and analyzed. The result showed that the complete cp genome of C. lipskyi was 151,244 bp in length, consisting of a large single-copy (LSC) region of 82,908 bp, a small single-copy (SSC) region of 18,430 bp, and a pair of inverted repeats (IRs) of 24,953 bp. The overall GC content of the C. lipskyi is 37.68%. The species of C. lipskyi possessed 127 genes, including 83 protein-coding genes, 36 transfer RNA genes, and eight ribosomal RNA genes. The present study found that Inula is sister groups with the closest genetic relationship. The obtained knowledge could provide useful information for future phylogenetic, taxonomic, and evolutionary studies on Inuleae.